Mengoptimalkan Kepatuhan Terhadap Prinsip-Prinsip Syariah dan Meningkatkan Kepercayaan Konsumen Melalui Pendampingan Sertifikasi Label Halal Pada UMKM - N, As Syifa’ Khoirun; Ulum, Bahrul; Noviansyah, Arvi; Tiyani, Arwhilan; P, Asti Elysia; Fikriyah, Ashfa (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
This service aims to increase consumer confidence in Pitik Poky MSME products in Kediri City through assistance in renewing halal label certification. This effort also aims to ensure compliance with sharia principles in the product production and distribution processes. The service approach is carried out through a series of training and consultation activities with Pitik Poky MSME owners. The service team provides guidance regarding halal certification requirements, assists in collecting documents, and provides direction regarding improving production processes in accordance with sharia principles. Through this assistance, Pitik Poky MSMEs succeeded in renewing their halal label certification, increasing consumer confidence, and ensuring compliance with sharia principles. The certification update also opens up new access to markets that prioritize halal products, providing a positive impact on the growth and development of these MSMEs.